Salt bath composition for high-temperature strengthening of lithium aluminum silicon glass and use method of salt bath composition
Patent Information
- Application Number
- CN202411726751.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
Smart Images

Figure CN119528457A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of chemical strengthening of lithium aluminosilicate glass, in particular to the field of salt bath compositions for high-temperature chemical strengthening of lithium aluminosilicate glass, and specifically to a salt bath composition for high-temperature strengthening of lithium aluminosilicate glass and a method for using the same. Background Art
[0002] With the development of chemically strengthened glass technology, lithium aluminum silicon glass-ceramics has been widely used in fields such as mobile phone covers, computer screen savers, and touch-screen electronic panels due to its excellent drop resistance and good acid and alkali resistance, and the market demand continues to grow. However, in this context, high-temperature strengthening has gradually become the mainstream trend in the industry as an effective means to improve glass performance. Higher strengthening temperatures can not only significantly shorten the strengthening time and improve production efficiency, but also significantly enhance the surface compressive stress (CS) of the glass, increase the thickness of the ion exchange layer (DOL), and effectively reduce the central tensile stress (CT). With the combined effect of these improvements, the surface hardness of the glass is improved, and the scratch resistance and drop resistance are also enhanced.
[0003] However, the high-temperature strengthening process also exposes some problems that cannot be ignored. First, the commonly used nitrate salt bath composition is more likely to decompose under high temperature conditions, producing a series of corrosive impurities, such as nitrite ions and alkali metal oxides (such as potassium oxide, sodium oxide, etc.). These impurities have a strong corrosive effect on the surface of the strengthened glass, causing various defects on the glass surface. In particular, after the salt bath has been used for a period of time, the cumulative effect of corrosive impurities becomes more and more obvious, which will make the molecular structure of the glass surface being strengthened become uneven, thereby causing scattering and eventually forming a "rainbow pattern" defect.
[0004] In order to solve the problem of defects on the glass surface, the prior art attempts to improve the quality of the glass surface through deeper polishing. Although this method can eliminate rainbow lines to a certain extent, over-deep polishing will damage the high stress layer on the glass surface, reduce its stress depth, and thus weaken the strength of the glass. For some special shapes of 3D hot-bent glass, more complex re-polishing processes are required, which not only increases the difficulty of production, but also further raises the production cost. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a salt bath composition for high-temperature strengthening of lithium aluminosilicate glass and a method for using the same, aiming to increase the high-temperature decomposition temperature of the salt bath composition, while strengthening the glass at high temperature without producing rainbow patterns, significantly shortening the chemical strengthening time, increasing the surface compressive stress, deepening the depth of the ion exchange layer, and at the same time extending the service life of the salt bath composition for chemical strengthening, thereby solving the problem of rainbow pattern defects in lithium aluminosilicate glass during high-temperature chemical strengthening from the root.
[0006] In order to solve the above technical problems, in the first aspect, the present application proposes a salt bath composition for high-temperature strengthening of lithium aluminosilicate glass, comprising KNO3, NaNO3 and Na2SO4, wherein, in the salt bath composition, calculated by molar percentage, the content of KNO3 is 1.18-88.9 mol%, the content of Na2SO4 is 11.00-26.00 mol%, and the content of NaNO3 is 0.10-87.82 mol%; the molar percentages of KNO3, NaNO3 and Na2SO4 in the salt bath composition satisfy the following relationship: 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.35; the salt bath composition basically does not contain carbonates and / or chlorides.
[0007] Furthermore, the melting point of the salt bath composition is not higher than 550°C, preferably, the melting point is 450°C to 550°C.
[0008] Furthermore, the decomposition temperature of the salt bath composition is above 550°C.
[0009] Furthermore, the decomposition temperature of the salt bath composition is 550-700°C, and more preferably the decomposition temperature is 550-600°C.
[0010] Furthermore, the melting point of the salt bath composition is not higher than 550°C, and the decomposition temperature thereof is above 550°C.
[0011] Furthermore, the salt bath composition is one of a ternary system eutectic composition, a quaternary system eutectic composition, and a quinary system eutectic composition.
[0012] Furthermore, the salt bath composition is a ternary eutectic composition of KNO3, NaNO3 and Na2SO4.
[0013] Furthermore, the Na in the salt bath composition + With K + The molar ratio is (20:80) to (99:1).
[0014] Furthermore, the molar percentage relationship formula of KNO3, NaNO3 and Na2SO4 in the salt bath composition is: 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.33.
[0015] Furthermore, the temperature of high temperature strengthening is 450°C or higher, and preferably the temperature of high temperature strengthening is 450°C to 600°C.
[0016] In a second aspect, the present application proposes a method for preparing a salt bath composition for high temperature strengthening of lithium aluminosilicate glass as described above, comprising the following steps:
[0017] The molten salt components are dried and dehydrated, then mixed evenly in a container, heated until all the solid molten salt is melted, then kept constant at the melting temperature for a certain period of time, and then naturally cooled to room temperature to obtain a salt bath composition; the salt bath composition includes KNO3, NaNO3 and Na2SO4.
[0018] Furthermore, the constant temperature time is 0.5-10h.
[0019] In a third aspect, the present application proposes a method for using the lithium aluminosilicate glass high temperature strengthening salt bath composition as described above, comprising the following steps:
[0020] The salt bath composition is added into a strengthening furnace for heating and melting, and then an additive is added; the preheated glass is then transferred into the salt bath composition for chemical strengthening; the additive is one or more of LiNO3, silicic acid, and ion sieve.
[0021] Further, the glass includes the following components, in terms of molar percentage of oxides: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: 0.50mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%.
[0022] Furthermore, according to the mass percentage calculation based on the total mass of the salt bath composition, the content of LiNO3 is 0-0.2wt%; the content of silicic acid is 0.01wt%-0.5wt%; and the content of the ion sieve is 0.5wt%-2wt%.
[0023] Furthermore, the Na in the salt bath composition + With K + The molar ratio is (20:80) to (99:1).
[0024] Further, the melting temperature is not higher than 550°C, preferably, the melting temperature is not higher than 540°C.
[0025] Furthermore, the process of adding the additive includes first adding LiNO3 and then adding silicate to stand and clarify.
[0026] Furthermore, the preheating process is to place the glass and the ion sieve in a preheating furnace for preheating, and then put the glass and the ion sieve into the salt bath composition for strengthening.
[0027] Furthermore, the preheating temperature is 300°C to 370°C.
[0028] Compared with the prior art, this application has the following beneficial effects:
[0029] 1. The present application adjusts the component types and dosages of the salt bath composition, and finds that the adjusted salt bath composition has both a melting point of no higher than 550°C and a high thermal stability of more than 550°C, that is, its decomposition temperature is above 550°C (calculated based on a 3% decrease in mass); this feature enables the salt bath composition to maintain good solubility and thermal stability under high temperature conditions, and can melt at high temperatures without decomposing due to excessively high temperatures, thereby ensuring the smooth progress of the chemical strengthening process.
[0030] 2. The salt bath composition described in the present application can be more efficiently chemically strengthened. The salt bath composition can be melted under strengthening conditions of at least 450°C, which significantly shortens the chemical strengthening time of the glass. This means that under the same production conditions, the glass strengthening process can be completed faster, thereby improving production efficiency. At the same time, the salt bath composition can significantly increase the compressive stress on the glass surface, deepen the compressive stress layer, and make the thickness of the compressive stress layer of the glass exceed 140 μm (glass thickness: 0.69 mm), thereby significantly improving the scratch resistance and drop resistance of the glass.
[0031] 3. The salt bath composition strengthened glass described in the present application, especially the lithium aluminum silicate glass strengthened at high temperature, does not produce corrosive impurities during use, thus avoiding the appearance of rainbow defects on the glass surface; rainbow defects not only affect the light transmittance and visual effect of the glass, but may also have an adverse effect on the user's eyesight; by eliminating this defect, the present application significantly improves the yield of glass products, reduces the scrap rate, and reduces production costs.
[0032] 4. The salt bath composition described in the present application has a long service life. Even after repeated use, its performance remains stable and will not cause corrosion problems due to the accumulation of impurities. The salt bath composition of the present application has significantly improved the efficiency and quality of glass chemical strengthening and reduced production costs through its melting point not higher than 550°C, high thermal stability, efficient chemical strengthening effect, elimination of rainbow defects and extended service life, and other innovations, and has important application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the surface of a reinforced glass-ceramic without rainbow patterns.
[0034] Figure 2 This is a scanning electron microscope image of the surface of a strengthened glass-ceramic with rainbow defects.
[0035] Figure 3 The curves of mass loss rate of the salt bath compositions of Example 4 and Comparative Example 3 during the insulation process at 600° C. versus time are shown.
[0036] Figure 4 This is the thermogravimetric curve of Example 1.
[0037] Figure 5 This is the thermogravimetric curve of Example 2.
[0038] Figure 6 This is the thermogravimetric curve of Example 3. DETAILED DESCRIPTION
[0039] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0040] Unless otherwise specified in specific circumstances in this application, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when the range is limited. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0041] As used herein, the language "substantially free of" or "free of" when used to describe constituent components of a composition, batch, melt or article refers to constituent components that have not been actively added or dosed into the composition, batch, melt or article but may be present in small amounts of less than about 0.01% (on an oxide mole basis) as a contaminant and / or due to the inherent degree of uncertainty attributable to any measurement or analytical technique.
[0042] The corresponding test methods and related measurement methods involved in this application are explained as follows:
[0043] Depth of compressive stress layer DOL_0: refers to the depth position in the strengthened glass-ceramics where the compressive stress generated by the strengthening process reaches zero.
[0044] Tensile stress line density CT_LD: The ratio of the tensile stress integral to the thickness of the glass in its thickness section is obtained by SLP stress instrument test. The compressive stress and tensile stress in chemically strengthened glass are in a balanced and equal relationship, and the SLP-100 stress instrument is more accurate in testing the tensile stress area of glass. Therefore, the tensile stress integral to thickness ratio is used to characterize the stress size contained in the unit thickness of the glass, which is used to characterize the stress degree of chemically strengthened glass.
[0045] CT_AV: refers to the average value of all tensile stresses in the tensile stress zone.
[0046] Test conditions for DOL_0, CT_AV, and CT_LD: Use SLP-2000 from Japan Orihara for testing, light source wavelength is 518nm, photoelastic coefficient = 25.5 (nm / cm) / MPa, refractive index = 1.54, exposure time: 300usec. During the test, it is necessary to drop a special refractive liquid on the corresponding stress meter, then wipe the tempered microcrystalline glass product clean, place it on the test path, and test its value. Among them, the refractive index of the refractive liquid used by SLP-2000 is 1.51.
[0047] Vickers hardness test: Use a microhardness tester to measure the Vickers hardness HV (kgf / mm) of the glass surface after chemical strengthening. 2 ), the test pressure is 300g and the holding time is 10s.
[0048] Glass thickness: Determined by micrometer test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0049] Tempered glass appearance inspection: Visually observe the tempered micro-ceramic glass under a white fluorescent light with an illumination of 2000 Lux. Keep the glass 1 cm to 3 cm away from the black background, tilt the glass 30 to 80 degrees, and observe at a distance of 30 cm to 50 cm from the glass surface.
[0050] Thermal gravimetric test of salt bath composition: first, the melted and uniformly cooled salt bath composition was placed in an oven at 120°C for 1 hour to remove water, and then an appropriate amount of sample was weighed and the thermogravimetric curve of the sample was tested using a Mettler Toledo TGA / DSC 3+ synchronous thermal analyzer. The heating rate was 5°C / min, the test temperature range was 30-900°C, and N2 atmosphere was used at a flow rate of 50mL / min.
[0051] The thermal decomposition temperature of the salt bath composition in the present application is defined as the temperature at which the mass loss on its thermal weight loss curve is 3%.
[0052] In the process of glass chemical strengthening, high temperature strengthening becomes a key means to improve production efficiency and glass performance. However, the commonly used nitrate salt bath composition is easy to decompose at high temperature, producing corrosive impurities such as nitrite ions and alkali metal oxides (such as potassium oxide, sodium oxide, etc.). These impurities will corrode the glass surface, resulting in uneven molecular structure, scattering phenomenon, and rainbow defects such as attached Figure 2 As shown, it seriously affects the light transmittance and visual effect of the glass, and even has an adverse effect on the user's vision. In addition, carbonates such as sodium carbonate and potassium carbonate will also cause rainbow lines to appear on the tempered glass, and will also cause fogging; chloride salts such as sodium chloride and potassium chloride, in which chloride ions will not only cause rainbow lines to appear on the tempered glass, but also corrode the tempering container such as the tempering furnace. At the same time, the accumulation of these impurities will also reduce the service life of the salt bath and increase production costs. Based on the melting phase diagram of the NaNO3-KNO3-Na2SO4 eutectic, this application found that mixing Na2SO4 with a higher melting point (884°C) and sodium nitrate and potassium nitrate with a low melting point can achieve a melting point of no more than 550°C at a specific ratio; in addition, by adjusting the content of Na2SO4, the decomposition temperature of the NaNO3-KNO3-Na2SO4 eutectic is ensured to exceed 550°C; and thus the salt bath composition can be melted at the use temperature when in use, and its decomposition temperature is above the use temperature, and no decomposition will occur, which will not cause the tempered glass to produce rainbow line defects during the chemical strengthening process.
[0053] From the above viewpoints, in order to increase the high-temperature decomposition temperature of the salt bath composition, strengthen the glass at high temperature without producing rainbow lines, significantly shorten the chemical strengthening time, increase the surface compressive stress, deepen the depth of the ion exchange layer, and at the same time extend the service life of the salt bath composition for chemical strengthening, the present application provides a salt bath composition for high-temperature strengthening of lithium aluminosilicate glass, including KNO3, NaNO3 and Na2SO4, wherein, calculated by molar percentage, the content of KNO3 is 1.18-88.90 mol%, the content of Na2SO4 is 11.00-26.00 mol%, and the content of NaNO3 is 0.10-87.82 mol%; the molar percentages of KNO3, NaNO3 and Na2SO4 in the salt bath composition satisfy the following relationship: 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.35; the salt bath composition substantially does not contain carbonates and / or chlorides.
[0054] Na2SO4 is one of the components of the salt bath composition. It has a high melting point (884°C), which can increase the eutectic point of the enhanced salt bath and weaken the polarization effect of metal cations on nitrate ions. However, if the amount is too high, the eutectic point of the salt bath will be raised too high, making it difficult to melt the salt bath. The addition of Na2SO4 can adjust the ratio of KNO3 and NaNO3 to ensure that K+ and Na + balance, thereby optimizing the ion exchange process and promoting K + With Na in glass + Rapid exchange increases the surface compressive stress of the glass and the depth of the ion exchange layer. Na2SO4 is relatively stable at high temperatures and will not decompose to produce impurities. In some embodiments of the present application, the content of Na2SO4 is 11.00-26.00 mol%, calculated as a mole percentage. In some embodiments of the present application, the content of Na2SO4 can be 11.00 mol%, 11.10 mol%, 11.30 mol%, 11.60 mol%, 12.20 mol%, 12.50 mol%, 12.60 mol%, 12.80 mol%, 13.00 mol%, 13.10 mol%, 13.30 mol%, 13.50 mol%, 13.70 mol%, 13.80 mol%, 13.90 mol%, 14.10 mol%, 14.20 mol%, 14.30 mol%, 14.40 mol%, 14.50 mol%, 14.60 mol%, 14.70 mol%, 14.80 mol%, 14.90 mol%, 14.15 mol%, 14.20 mol%, 14.30 mol%, 14.40 mol%, 14.50 mol%, 14.70 mol%, 14.80 mol%, 14.90 mol%, 14.15 .90mol%, 14.00mol%, 14.20mol%, 14.50mol%, 14.70mol%, 14.90mol%, 15.00mol%, 15.20mol%, 15.40m ol%, 15.60mol%, 15.80mol%, 16.00mol%, 16.30mol%, 16.50mol%, 16.70mol%, 16.90mol%, 17.00mol%, 17.20mol%, 17.50mol%, 17.70mol%, 17.90mol%, 18.00mol%, 18.50mol%, 18.80mol%, 19.00mol%, 19.3 0mol%, 19.50mol%, 19.80mol%, 20.00mol%, 20.50mol%, 20.80mol%, 21.00mol%, 21.50mol%, 21.80mol %, 22.00mol%, 22.10mol%, 22.50mol%, 22.80mol%, 23.10mol%, 23.60mol%, 23.90mol%, 24.10mol%, 24.60mol%, 24.90mol%, 25.20mol%, 25.60mol%, 25.80mol% or 26.00mol%, or in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in embodiments, any of the above ranges can be combined with any other ranges.
[0055] KNO3 is one of the components of the salt bath composition and can provide sufficient K + The content can meet the K + Ions and Na in Glass +Rapid exchange is performed to increase the surface compressive stress CS of the glass. In some embodiments of the present application, the content of KNO3 is 1.18-88.90 mol% calculated by mole percentage. In some embodiments of the present application, the content of KNO3 can be 1.18 mol%, 1.50 mol%, 1.80 mol%, 2.00 mol%, 2.20 mol%, 2.80 mol%, 3.20 mol%, 3.70 mol%, 3.90 mol%, 4.20 mol%, 4.80 mol%, 5.00 mol%, 5.60 mol%, 5.90 mol%, 6.10 mol%, 6.80 mol%, 7.10 mol%, 7.60 mol%, 7.90 mol%, 8.10 mol%, 8.70 mol%, 8.90 mol%, 9. 10mol%, 9.60mol%, 9.90mol%, 10.10mol%, 10.90mol%, 11.10mol%, 11.80mol%, 12.10mol%, 12.80mol%, 13.00mol%, 13.50mol%, 14.00mol%, 14 .50mol%, 15.00mol%, 15.50mol%, 16.00mol%, 16.50mol%, 17.00mol%, 17.50mol%, 18.00mol%, 18.50mol%, 19.00mol%, 19.50mol%, 20.00mol% , 20.50mol%, 21.00mol%, 21.50mol%, 22.00mol%, 22.50mol%, 23.00mol%, 23.50mol%, 24.00mol%, 24.50mol%, 25.00mol%, 25.50mol%, 26.00 mol%, 26.50mol%, 27.00mol%, 27.50mol%, 28.00mol%, 28.30mol%, 28.90mol%, 30.00mol%, 31.00mol%, 32.00mol%, 33.00mol%, 35.00mol%, 38 .00mol%, 40.00mol%, 43.00mol%, 46.00mol%, 48.00mol%, 50.00mol%, 51.60mol%, 55.60mol%, 58.50mol%, 60.90mol%, 65.90mol%, 70.90mol%, 74.80mol%, 75.90mol%, 78.50mol%, 80.00mol%, 82.00mol%, 84.00mol%, 86.00mol%, 88.00mol% or 88.90mol%, or in a numerical range consisting of any two of the above specific values as endpoints.It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.
[0056] NaNO3 is one of the components of the salt bath composition. + The content can ensure sufficient Na + With Li in glass + exchange, thereby increasing the depth of the ion exchange layer. + If the content is too low, the corresponding K + Excessive content affects Na + With Li + The exchange of Na will reduce the depth of the ion exchange layer. + If the content is too high, the corresponding K + The content is too low, affecting K + with Na + The exchange reduces the surface compressive stress CS of the glass. In some embodiments of the present application, the content of NaNO3 is 0.10-87.82 mol% calculated as a mole percentage. In some embodiments of the present application, the content of NaNO3 can be 0.10 mol%, 0.50 mol%, 1.00 mol%, 2.00 mol%, 3.00 mol%, 4.00 mol%, 5.00 mol%, 7.00 mol%, 9.00 mol%, 10.00 mol%, 13.00 mol%, 17.00 mol%, 19.00 mol%, 20.00 mol%, 25.00 mol%, 28.00 mol%, 31.00 mol%, 36.00 mol%, 37.00 mol%, 38.00 mol%, 39.00 mol%, 40.00 mol%, 41.00 mol%, 42.00 mol%, 43.00 mol%, 44.00 mol%, 45.00 mol%, 46.00 mol%, 47.00 mol%, 48.00 mol%, 49.00 mol%, 50.00 mol%, 51.00 mol%, 52.00 mol%, 53.00 mol%, 54.00 mol%, 55.00 mol%, 56.00 mol%, 57.00 mol%, 58.00 mol%, 59.00 mol%, 60.00 mol%, 61.00 mol%, 62.00 mol%, 63.00 mol%, 64.00 mol%, 65.00 mol%, 66.00 mol%, 67.00 mol%, 68.00 mol%, 69 %, 39.00mol%, 43.00mol%, 46.00mol%, 49.00mol%, 53.00mol%, 57.00mol%, 59.00mol%, 62.00mol%, 65.00mol%, 69.00mol%, 72.00mol%, 78.00mol%, 82.00mol%, 84.00mol%, 84.80mol%, 85.60mol%, 87.00mol% or 87.90mol%, or be in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in embodiments, any of the above ranges can be combined with any other ranges.
[0057] The present application also studies the relationship between KNO3, NaNO3 and Na2SO4 in the salt bath composition, and finds that by adjusting the molar ratio between NaNO3, KNO3 and Na2SO4, the decomposition temperature of the salt bath composition can be greatly improved, thereby making the decomposition temperature of the salt bath composition above 550°C. In some embodiments of the present application, the molar percentage relationship formula of KNO3, NaNO3 and Na2SO4 in the salt bath composition is Na2SO4 / (NaNO3+KNO3), which is specifically 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.35. In some embodiments of the present application, in the salt bath composition, Na2SO4 / (NaNO3+KNO3) may be 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.31, 0.32, 0.33, 0.34 or 0.35, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in embodiments, any of the above ranges may be combined with any other ranges.
[0058] In the present application, the salt bath composition substantially does not contain carbonates and / or chlorides. "Substantially does not contain" means that the salt bath composition of the present application does not actively add substances containing carbonates and / or chlorides, and the content of carbonates and / or chlorides as impurities is less than 1000ppm. In the present application, carbonates are, for example, potassium carbonate, sodium carbonate, lithium carbonate, etc., and chlorides are, for example, potassium chloride, sodium chloride, lithium chloride, etc. In some embodiments of the present application, carbonates are at least one of potassium carbonate, sodium carbonate and lithium carbonate. In some embodiments of the present application, chlorides are at least one of potassium chloride, sodium chloride and lithium chloride.
[0059] In some embodiments of the present application, the melting point of the salt bath composition is not higher than 550°C, preferably 450°C to 550°C. In some embodiments of the present application, the melting point of the salt bath composition may be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in embodiments, any of the above ranges may be combined with any other ranges.
[0060] In some embodiments of the present application, the decomposition temperature of the salt bath composition can reach 550°C or above, preferably 550-700°C, and more preferably 550-600°C. In some embodiments of the present application, the decomposition temperature of the salt bath composition can be 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0061] In some embodiments of the present application, the melting point of the salt bath composition is not higher than 550°C, and its decomposition temperature is above 550°C. In some embodiments of the present application, the melting point of the salt bath composition may be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C, or in a numerical range consisting of any two of the above specific values as endpoints; and at the same time, the decomposition temperature of the salt bath composition may be 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.
[0062] In the present application, potassium sulfate, lithium sulfate, etc. can also be added to the salt bath composition to form a quaternary eutectic composition and a quinary eutectic composition, and used as a salt bath for strengthening glass, which can achieve the technical effect of the present application. In some embodiments of the present application, the salt bath composition is one of a ternary eutectic composition, a quaternary eutectic composition, and a quinary eutectic composition. In the present application, the quaternary eutectic composition is, for example, NaNO3-KNO3-Na2SO4-K2SO4 eutectic, and the quinary eutectic composition is, for example, NaNO3-KNO3-Na2SO4-K2SO4-Li2SO4 eutectic. In some embodiments of the present application, calculated by molar percentage, KNO3: 0.1~79mol%, K2SO4: 0~19mol%, Na2SO4: 6~21mol%, NaNO3: 0.1~87mol% in the NaNO3-KNO3-Na2SO4-K2SO4 eutectic. In some embodiments of the present application, calculated by molar percentage, in the NaNO3-KNO3-Na2SO4-K2SO4-Li2SO4 eutectic, KNO3: 0.1~79mol%, K2SO4: 0~19mol%, Na2SO4: 6~21mol%, NaNO3: 0.1~87mol%, Li2SO4: 0~1mol%.
[0063] In the salt bath composition, Na + With K + The molar ratio of Na + Ions and Li in Glass + For fast exchange, and K + With Na in glass + Rapid exchange is performed to increase the surface compressive stress and ion exchange layer depth of the glass. In some embodiments of the present application, Na in the salt bath composition + With K + The molar ratio of Na in the salt bath composition is 20:80 to 99:1. + With K + The molar ratio of can be 20:80, 34:66, 50:50, 54:46, 74:26, 91:9, 98:2 or 99:1, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0064] In some embodiments of the present application, the temperature of high temperature strengthening is above 450°C, preferably 450°C to 600°C; more preferably 500°C to 600°C. In some embodiments of the present application, the temperature of high temperature strengthening is 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 580°C, 590°C or 600°C, or is in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0065] The present application provides a method for preparing the above-mentioned salt bath composition for high-temperature strengthening of lithium aluminosilicate glass, comprising the following steps:
[0066] The molten salt components are dried and dehydrated, then mixed evenly in a container, heated until all the solid molten salt is melted, then kept constant at the melting temperature for a certain period of time, and then naturally cooled to room temperature to obtain a salt bath composition; the salt bath composition includes KNO3, NaNO3 and Na2SO4.
[0067] In some embodiments of the present application, the time of constant temperature is 0.5-10.0h. In some embodiments of the present application, the time of constant temperature can be 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h, 8.5h, 8.8h, 9.0h, 9.2h, 9.5h, 9.8h or 10.0h, or be in the numerical range consisting of any two specific numerical values as endpoints. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0068] The present application provides a method for using the salt bath composition for high-temperature strengthening of lithium aluminosilicate glass as described above, comprising the following steps: adding the salt bath composition to a strengthening furnace for heating and melting, and then adding an additive; thereafter transferring the preheated glass to the salt bath composition for chemical strengthening; the additive is one or more of LiNO3, silicic acid, and ion sieve.
[0069] In the present application, the glass is common ordinary glass, microcrystalline glass, strengthened glass, etc. in the art, and the salt bath composition can be used for chemical strengthening. In some embodiments of the present application, the glass includes the following components in terms of molar percentage of oxides: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: 0.50mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%.
[0070] In this application, adding an appropriate amount of LiNO3 to the initial salt bath can regulate the Li + -Na + The speed of exchange, Li + The concentration is too low, Li + -Na + If the exchange speed is too fast, there is a risk of glass cracking. + Concentration is too high, Li + -Na + If the exchange rate is too slow, it will increase the strengthening time and reduce the production efficiency. In some embodiments of the present application, the content of LiNO3 is 0-0.20wt%, preferably 0.02-0.10wt%, calculated by mass percentage according to the total mass of the salt bath composition. In some embodiments of the present application, the content of LiNO3 can be 0, 0.02wt%, 0.03wt%, 0.05wt%, 0.07wt%, 0.09wt%, 0.10wt%, 0.12wt%, 0.14wt%, 0.15wt%, 0.17wt%, 0.18wt%, 0.19wt% or 0.20wt%, or in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0071] In the present application, silicate is used to regulate the pH value of the salt bath so that the pH value of the salt bath is maintained in a reasonable range suitable for glass strengthening. In some embodiments of the present application, after adding silicate to the salt bath composition, it is left to stand for clarification. In some embodiments of the present application, the temperature for standing for clarification is 450-550°C, and the time for standing for clarification is 12-36h. In some embodiments of the present application, the content of silicate is 0.01wt% to 0.50wt%, preferably 0.02wt% to 0.50wt%, according to the total mass of the salt bath composition. In some embodiments of the present application, the content of silicate is calculated as a mass percentage according to the total mass of the salt bath composition, and can be 0.01wt%, 0.02wt%, 0.04wt%, 0.06wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.20wt%, 0.30wt%, 0.40wt% or 0.50wt%, or in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.
[0072] In this application, the ion sieve is used to adsorb Li + Prevent "salt bath poisoning". There is no restriction on the timing of adding the ion sieve, and the ion sieve can be added to the salt bath at the same time as the glass, or added to the salt bath successively with the glass. In some embodiments of the present application, the glass and the ion sieve are placed in a preheating furnace for preheating, and then the glass and the ion sieve are put into the salt bath composition together for chemical strengthening. In some embodiments of the present application, the preheating temperature is 300°C to 370°C. In some embodiments of the present application, the preheating temperature may be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C or 370°C, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the implementation scheme, any of the above ranges may be combined with any other ranges.
[0073] In the present application, the composition of the ion sieve is SiO2: 38-4%, Al2O3: 2-16%, Na2O: 30-45%, Y2O3: 0-2%, ZrO2: 0-3%, K2O: 0-3%, B2O3: 0-3%. In some embodiments of the present application, the content of the ion sieve is 0.5wt%-2.0wt% according to the mass percentage calculated by the total mass of the salt bath composition. In some embodiments of the present application, the content of the ion sieve can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2.0wt%, or in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0074] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0075] Example 1
[0076] The raw material components of Example 1 in Table 1 were dried and dehydrated, then mixed evenly in a mixer, heated until the solid molten salt was completely melted, then kept constant at the melting temperature for 2 hours, and then naturally cooled to room temperature to obtain a salt bath composition.
[0077] Embodiment 2-8
[0078] The operation was carried out under the same conditions as in Example 1, except that the raw material compositions for preparing the salt bath composition were shown in Tables 1 and 2.
[0079] Comparative Examples 1-7
[0080] The operation was carried out under the same conditions as in Example 1, except that the raw material compositions for preparing the salt bath composition were as shown in Tables 1-3.
[0081] The performance tests were conducted on the salt bath compositions of Examples 1-8 and Comparative Examples 1-7. The results are shown in Tables 1-3.
[0082] Table 1
[0083]
[0084] Table 2
[0085]
[0086] As can be seen from Tables 1 to 2, the NaNO3-KNO3-Na2SO4 eutectic can achieve a eutectic point of no more than 550°C within the molar percentage range of the present application according to the melting phase diagram, and the specific eutectic point is 450 to 550°C.
[0087] Compared with Comparative Examples 1-2, the present embodiment of the present invention can adjust the content of each raw material component in the NaNO3-KNO3-Na2SO4 system, especially adjust the ratio of Na2SO4 / (NaNO3+KNO3), so that the decomposition temperature of the salt bath composition can be adjusted within the range of 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.35, thereby making the eutectic point of the salt bath composition not exceed 550°C and the decomposition temperature above 550°C. In Comparative Example 1, Na2SO4 is not added, and its eutectic point and decomposition temperature are the lowest among all compositions; although Na2SO4 is added to Comparative Example 2, the amount added is too low to significantly increase the decomposition temperature; Comparative Example 3 also does not add Na2SO4, and the content of NaNO3 and KNO3 in Comparative Example 3 is also not within the range described in the present application, which further illustrates that the prior art uses raw material components of NaNO3 and KNO3 as salt bath compositions, which cannot meet the requirements of the present application.
[0088] The salt bath compositions of Example 4 and Comparative Example 3 in Table 2 were kept at 600° C., and the obtained mass-time curves were as follows: Figure 3 As shown. Figure 3 It can be seen that at 600℃, in Na + :K + Under the same molar ratio, the weight loss rate of Example 4 is always maintained at a low level and is significantly lower than that of Comparative Example 3. It can be seen that the thermal stability of the salt bath composition prepared by using NaNO3-KNO3-Na2SO4 in Example 4 is better than that of the salt bath composition prepared by using NaNO3-KNO3 in Comparative Example 3.
[0089] Table 3
[0090]
[0091] As can be seen from Table 3, a salt bath composition with a eutectic point of 500° C. can also be prepared by mixing carbonates such as potassium carbonate and chlorides such as potassium chloride and sodium chloride with nitrates.
[0092] In addition, the salt bath composition of Example 1 was added to a strengthening furnace for heating and melting, and then 0.02wt% of silicate was added to the total mass of the salt bath composition for mixing, and then the mixture was allowed to stand at 480°C for clarification for 24h. 0.03wt% of LiNO3 was added to the total mass of the salt bath composition, and then an ion sieve was added, and the content of the ion sieve was 1.00wt% of the total mass of the salt bath composition. After that, each batch of microcrystalline glass preheated at 370°C was sequentially placed in the salt bath composition for chemical strengthening, the chemical strengthening temperature was 500°C, and the chemical strengthening time was 6h; the composition of the microcrystalline glass was SiO2: 68.50mol%, Al2O3: 3.9mol%, P2O5: 1.1mol%, ZrO2: 2.60mol%, Na2O: 0.5mol%, K2O: 0.40mol%, Li2O: 21.6%, CaO: 0.90mol%, B2O3: 0.50mol%.
[0093] The process for chemically strengthening glass in Examples 2 and 4-8 is the same as that in Example 1.
[0094] The process for chemically strengthening the glass in Comparative Examples 1 and 4-7 is the same as that in Example 1.
[0095] The chemically strengthened strengthened glass-ceramics of each embodiment and comparative example were naturally cooled, then cleaned and dried, and then subjected to performance tests and defect inspections. The results are shown in Tables 4-6. The rainbow defects are as follows: Figure 2 shown.
[0096] Table 4 Chemical strengthening conditions of glass-ceramics and performance parameters of strengthened glass-ceramics
[0097]
[0098] It can be seen that when the salt bath composition of Example 1-2 is used as a salt bath to strengthen the microcrystalline glass at 500°C, compared with the salt bath composition of Comparative Example 1, no nitrate decomposition occurs to produce sodium oxide and potassium oxide to corrode the glass. Even after strengthening multiple batches of glass, no rainbow defects are produced on the surface of the strengthened glass, and the product qualification rate reaches 100%; while when the salt bath composition of Comparative Example 1 is used to chemically strengthen the microcrystalline glass, rainbow defects are found on the surface of the strengthened glass obtained after the second batch of chemical strengthening, which indicates that the salt bath composition of Comparative Example 1 decomposes at the chemical strengthening temperature (500°C) and produces substances that can corrode the glass, thereby causing rainbow defects on the surface of the strengthened glass. At the same time, the performance of the strengthened glass obtained by chemically strengthening the glass using Examples 1-2 as a salt bath is comparable to that of the strengthened glass obtained by chemically strengthening the glass using the conventional salt bath of Comparative Example 1, which indicates that the salt bath composition described in the present application can provide sufficient chemical strengthening effect for the glass.
[0099] Table 5
[0100]
[0101] As can be seen from Table 5, Examples 4-8, as salt bath compositions, chemically strengthen glass-ceramics without causing rainbow defects on the surface of the strengthened glass. In addition, as long as 20:80≤Na + (mol%):K + (mol%)≤99:1, change Na + (mol%):K + The ratio of (mol%) has almost no effect on the chemical strengthening effect of the glass, and the performance of the strengthened microcrystalline glass obtained is equivalent, which also proves that the addition of Na2SO4 in the salt bath composition does not affect the chemical strengthening effect provided by the salt bath composition for the microcrystalline glass.
[0102] Table 6
[0103]
[0104] It can be seen from Tables 3 to 6 that, compared with the KNO3-NaNO3-Na2SO4 salt bath composition system, the addition of carbonates and chlorides has, to a certain extent, increased the eutectic point of the salt bath composition to above 450°C. At the same time, these salt bath compositions introduce corrosive carbonates and chloride ions, which cause rainbow defects in the chemically strengthened tempered glass. In addition, after chemical strengthening with the addition of carbonates, fogging defects also appear on the surface of the tempered glass. The salt bath composition with the addition of chlorides also severely corrodes the strengthening furnace, resulting in a shortened service life of the equipment.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A salt bath composition for high temperature strengthening of lithium aluminosilicate glass, characterized in that: The salt bath composition comprises KNO3, NaNO3 and Na2SO4; wherein, in the salt bath composition, calculated by mole percentage, the content of KNO3 is 1.18-88.9 mol%, the content of Na2SO4 is 11-26 mol%, and the content of NaNO3 is 0.1-87.82 mol%; The molar percentages of KNO3, NaNO3 and Na2SO4 in the salt bath composition satisfy the following relationship: 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.35; The salt bath composition is substantially free of carbonate and / or chloride salts.
2. The salt bath composition according to claim 1, characterized in that The melting point of the salt bath composition is not higher than 550°C, preferably, the melting point is 450°C to 550°C.
3. The salt bath composition according to any one of claims 1 to 2, characterized in that The decomposition temperature of the salt bath composition is above 550°C.
4. The salt bath composition according to any one of claims 1 to 3, characterized in that The melting point of the salt bath composition is not higher than 550°C, and the decomposition temperature thereof is higher than 550°C.
5. The salt bath composition according to any one of claims 1 to 4, characterized in that The decomposition temperature of the salt bath composition is 550 to 700°C, and more preferably 550 to 600°C.
6. The salt bath composition according to any one of claims 1 to 5, characterized in that The salt bath composition is one of a ternary system eutectic composition, a quaternary system eutectic composition, and a quinary system eutectic composition.
7. The salt bath composition according to any one of claims 1 to 6, characterized in that The salt bath composition is a ternary system eutectic composition of KNO3, NaNO3 and Na2SO4.
8. The salt bath composition according to any one of claims 1 to 7, characterized in that The Na in the salt bath composition + With K + The molar ratio is (20:80) to (99:1).
9. The salt bath composition according to any one of claims 1 to 8, characterized in that The molar percentage relationship formula of KNO3, NaNO3 and Na2SO4 in the salt bath composition is: 0.12≤Na2SO4 / (NaNO3+KNO3)≤0.
33.
10. The salt bath composition according to any one of claims 1 to 9, characterized in that The temperature for high temperature strengthening of the salt bath composition is 450°C or higher, and preferably 450°C to 550°C.
11. A method for preparing the salt bath composition according to any one of claims 1 to 10, characterized in that: The steps include: The molten salt components are dried and dehydrated, then mixed evenly in a container, heated until all the solid molten salt is melted, then kept constant at the melting temperature for a certain period of time, and then naturally cooled to room temperature to obtain a salt bath composition; the salt bath composition includes KNO3, NaNO3 and Na2SO4.
12. The preparation method according to claim 11, characterized in that: The constant temperature time is 0.5 to 10 hours.
13. A method for using the salt bath composition according to any one of claims 1 to 10, comprising the following steps: The salt bath composition is added into a strengthening furnace for heating and melting, and then an additive is added; the preheated glass is then transferred into the salt bath composition for chemical strengthening; the additive is one or more of LiNO3, silicic acid, and ion sieve.
14. The method of use according to claim 13, characterized in that: In terms of molar percentage of oxides, the glass includes the following components: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: 0.50mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%.
15. The method of use according to claim 13, characterized in that: Calculated by mass percentage based on the total mass of the salt bath composition, the content of LiNO3 is 0-0.2wt%; the content of silicic acid is 0.01wt%-0.5wt%; and the content of the ion sieve is 0.5wt%-2wt%.
16. The method of use according to claim 13, characterized in that: The Na in the salt bath composition + With K + The molar ratio is (20:80) to (99:1).
17. The method of use according to claim 13, characterized in that: The melting temperature is not higher than 550°C, preferably, the melting temperature is not higher than 540°C.